Stationary dense operators in sequentially complete locally convex spaces - M. Kostic, S. Pilipovic, D. Velinov (Department of Mathematics and Informatics, Faculty of Sciences, University of Novi Sad, Serbia, 2017)
The purpose of this paper is to investigate the stationary dense operators and their connection to distribution semigroups and abstract Cauchy problem in sequentially complete spaces.
Keywords: stationary dense operators, distribution semigroups, ultradistribution semigroups, well-posedness, locally convex spaces